Muscular toxicity of colchicine combined with statins: a real-world study based on the FDA adverse event reporting system database from 2004–2023 - Liu, Ying; Wei, Chunyan; Yuan, Yanling; Zou, Dan; Wu, Bin (Frontiers in Pharmacology, 2024)
Background Through an analysis of the Food and Drug Administration Adverse Event Reporting System (FAERS), we explored the signal strength of adverse reactions (ADRs) related to myopathy caused by the combination of colchicine and statins and gained insight into the characteristics of these myopathy related ADRs. Methods We extracted data from the FAERS database about ADRs in individuals with myopathy resulting from the combination of colchicine and statins. The analysis was conducted for the period spanning from January 2004 to December 2023 using the reported odds ratio (ROR) and information component (IC) methods to assess muscle-related ADR signals. Results A total of 18,386 reports of statin myopathy-associated adverse reactions, 348 colchicine myopathy-associated adverse reactions, and 461 muscle-associated adverse reactions due to the combination of the two were collected; the strongest signals of statin myotoxicity events were for necrotizing myositis (ROR 50.47, 95% CL 41.74–61.01; IC 3.70 95% CL 3.25–4.08); the strongest signal for colchicine myotoxicity events was toxic myopathy (ROR 32.50, 95% CL 19.74–53.51; IC 4.97 95% CL 1.89–5.10), and the strongest signal for statins combined with colchicine was toxic myopathy (ROR 159.85, 95% CL 111.60–228.98; IC 7.22 95% CL 3.59–5.9); muscle-related adverse reactions signals were meaningful when the two drugs were combined in the order of colchicine combined with fluvastatin (ROR 187.38, 95% CL 96.68–363.17; IC 6.99 95% CL 1.65–5.68); colchicine combined with simvastatin in 135 cases (ROR 30.08. 95% CL 25.25–35.85; IC 4.80 95% CL 3.96–5.12); and colchicine combined with rosuvastatin (ROR 25.73, 95% CL 20.16–32.83; IC 4.59 95% CL 3.38–4.98) versus colchicine combined with atorvastatin (ROR 25.73, 95% CL 22.33–29.66; IC 4.59 95% CL 3.97–4.91) with almost identical signal intensity, followed by colchicine combined with pravastatin (ROR 13.67, 95% CL 9.17–20.37; IC 3.73 95% CL 1.87–4.47), whereas no signals were generated for lovastatin or pitavastatin. Conclusion Similar ADRs can occur when colchicine and statins are used individually or in combination; however, the strength of these reactions may differ. To minimize the risk of drug interactions, statins with less potential interactions, such as lovastatin, pitavastatin, and pravastatin, should be chosen, and myopathy-related indices and symptoms should be closely monitored during use.